Ultrasonographic evaluation of the fetal central nervous system: review of guidelines - Milani, Hérbene José Figuinha (Radiol Bras, 2019)
Central nervous system malformations constitute the second most common group of anomalies in fetuses. Such malformations have assumed clinical importance because of their association with high rates of perinatal morbidity and mortality. Therefore, it is extremely important to assess the fetal central nervous system during the prenatal period, in order to identify any changes in its development and thereby gain sufficient information to advise parents about pregnancy follow-up, options for fetal therapy, and the timing/type of delivery, as well as the postnatal treatment and prognosis. The objective of this review was to describe the ultrasonographic evaluation of the fetal central nervous system as per the guidelines of the International Society of Ultrasound in Obstetrics and Gynecology.